UV/oxidant degradation of pre-treated palm oil mill effluent in a photocatalytic fuel cell - Yap, Joyee Chun Ting (2022)
Attributable to the prosperous palm oil production growth in Malaysia, the generated palm oil mill effluent (POME) poses a high threat owing to its highly polluted characteristic. As the disposal of this effluent raised public environmental concern, POME pollution abatement and potential energy recovery from the effluent are flagged up as a research topic of interest. In this study, a new photocatalytic fuel cell system with employment of ZnO/Zn nanorod array photoanode, CuO/Cu cathode and persulfate oxidant was successfully designed to improve the degradation of organic pollutant in POME and simultaneous energy production. The photoelectrodes were fabricated and characterized by Field emission scanning electron microscopy with energy, X-ray diffraction, UV–Vis diffuse reflectance spectroscopy and Mott– Schottky plot analysis. Owing to the properties of strong oxidant of persulfate, the proposed PFC system has exhibited exceptional performance, increasing the chemical oxygen demand (COD) removal efficiency from 39.6% to 96.2% and amount of electricity generated from 5.7 to 35.6 mW/cm2 relative to the bare PFC system. The best PFC system performance was yielded under optimal conditions of 2.5mM of persulfate oxidant, POME dilution factor of 1:20 and natural solution pH of 8.51. Subsequently, a radical scavenging test was conducted, determining that the predominant radical species were sulfate radical (SO4 - •) and hydroxyl radical (•OH) contributed to effective removal of organics pollutant in POME and generation of electricity. The following recycling test affirmed the stability and durability photoanode after 4 continuous repetition usage and the cost analysis revealed the economic viability of PFC system serving as a post-treatment for degradation of POME. These findings contribute toward enhancing the sustainability criteria and economic viability of palm oil by adopting sustainable and efficient POME posttreatment technology.